Superior Wheat Yield and Profitability in Conservation Agriculture with Diversified Rotations vs. Conventional Tillage in Cold Arid Climates - Harun Cicek; Mia Schoeber; Irfan Gültekin; Tae Hoon Kim; Alexander Heer; Fevzi Partigöç; Rifat Zafer Arısoy; Şeref Aksoyak; Fatih Özdemir; Amritbir Riar (Land)
Wheat productivity in dry regions of the world such as Central Asia and the Mediterranean is experiencing significant declines due to erratic weather events. Conservation agriculture (CA) has been promoted as a promising alternative for drylands to address climate-change-induced water scarcity and soil degradation. A long-term experiment in the Central Anatolian region of Türkiye compared CA and conventional tillage (CT) using diversified two- and four-year rotations. All rotations outperformed the wheat–wheat control, with the highest yields in wheat–fallow and wheat–lentil rotations. Four-year rotations generally yielded more than two-year ones under both CA and CT, except wheat–fallow and wheat–lentil, which matched four-year results. In two-year-rotations, yield differences between CA and CT were largest in wheat–wheat and wheat–lentil, with CA increasing yields by around 50% and 60% for chickpea and lentil, respectively. Chickpea and lentil also had a similar positive effect on wheat yield in four-year rotations. All rotations were more profitable under CA than CT, with chickpea and lentil rotations achieving the highest gross margin. Soil organic matter content was significantly greater under CA compared to CT within each two-year crop rotation. Our study clearly demonstrated the advantages of CA over CT in terms of production, soil quality and economics.